Decadal evolution of a sandy beach adjacent to a river mouth under natural drivers and human impacts - Liu, Gen; Cai, Feng; Qi, Hongshuai; Liu, Jianhui; Cao, Chao; Zhao, Shaohua; He, Yanyu; Zhu, Jun; Yin, Chao; Mo, Wenyuan (Frontiers in Marine Science, 2024)
As escalating environmental pressures threaten the world’s beaches, understanding the driving factors influencing their geomorphological changes is of critical global importance. This study focuses on the morphological changes of Sigeng beach adjacent to Changhua River Mouth in Hainan Island, China through decadal monitoring of shoreline and profile topography and tries to illuminate the natural and anthropogenic factors that drove geomorphological changes. The results showed that Sigeng beach undergone significant changes between 2008 and 2024, with notable accretion at the northernmost and southernmost and general erosion at other sections. The shoreline change rates ranged between -18.4 m/yr and 13.0 m/yr, with the average rate of -1.9 m/yr, indicating overall erosion. The net longshore sediment transport (LST) rates along Sigeng beach was estimated through the combination of the cross-shore (profile) and longshore (shoreline) changes. The overall direction of net LST along the beach were southward, except for the northern section where the direction was northward due to the diffraction of NE waves by the long sand spit at the northernmost. The net LST rates at each profile varied from 0.8×104 m3/yr to 3.5×104 m3/yr. The main factors controlling Sigeng beach evolution, including seasonal wave action and reduction in fluvial sediment load, followed by sand spit and coastal structures, typhoon events, aeolian transport, and sea level rise, were discussed. Subsequently, adaptive protection measures, including beach nourishment, accompanied with groin system or multiple detached breakwaters were proposed to combat with beach erosion. The analysis presented in this study is helpful to understand the morphodynamics and to predict the future change of beaches.